Enhancing fresh-cut spinach preservation with carbon quantum dot-based composite coatings - Sijing Zhu; Linxuan Jin; Yueyue Zhang; Feiping Chen; Amr Farouk; Tao Yang; Guohui Yi; Houxue Li; Zhao-Jun Ban; Lingling Liu (Scientific Reports)
Abstract In order to address the issue of fresh-cut vegetable waste, this research was done on postharvest preservation techniques using carbon dots (CDs) and sericin protein (SC) composite coatings (SCCD). SCCD was synthesized using ultrasound technology, exhibiting promising antioxidant and antibacterial activities. The influence of CDs concentration variations on the morphological, fluorescence quenching, UV-shielding, and structural properties of SCCD was comprehensively investigated. Protein quenching caused by endogenous fluorescence was lessened by the interaction of SC and CDs. The inhibition zones grew from 7.8 to 19.21 mm and 20.01 mm, respectively, and the antibacterial activity of SCCD-1.0 rose by 146% (for B. subtilis) and 157% (for E. coli) in comparison to the SC. Additionally, the SCCD composite coating successfully delayed colonies expansion, preserved spinach flavor, decreased the fresh-cut spinach’s weight loss rate and malondialdehyde concentration in the storage experiment by 41.67% and 42.11%, respectively. These findings support the SCCD composite coating’s potential as an active food packaging material.